2021
DOI: 10.1021/acsami.0c20539
|View full text |Cite
|
Sign up to set email alerts
|

Alkali Dispersion in (Ag,Cu)(In,Ga)Se2 Thin Film Solar Cells—Insight from Theory and Experiment

Abstract: Silver alloying of Cu(In,Ga)Se 2 absorbers for thin film photovoltaics offers improvements in open-circuit voltage, especially when combined with optimal alkali-treatments and certain Ga concentrations. The relationship between alkali distribution in the absorber and Ag alloying is investigated here, combining experimental and theoretical studies. Atom probe tomography analysis is implemented to quantify the local composition in grain interiors and at grain boundaries. The Na concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 83 publications
1
29
0
Order By: Relevance
“…It was further found that the presence of Na in the absorber bulk plays a key role in the doping mechanism, usually leading to increased majority carrier densities. [63][64][65][66][67] As the solubility limit of Na in the ACIGS lattice (on V I ) increases with the Ag content, [68] it may be speculated that Na saturation is not reached during absorber processing, resulting in lower doping. Further studies are needed to reveal the exact relationship between doping, stoichiometry and Na distribution.…”
Section: Origin Of V Oc àJ Sc Anticorrelation With Varying Stoichiometrymentioning
confidence: 99%
“…It was further found that the presence of Na in the absorber bulk plays a key role in the doping mechanism, usually leading to increased majority carrier densities. [63][64][65][66][67] As the solubility limit of Na in the ACIGS lattice (on V I ) increases with the Ag content, [68] it may be speculated that Na saturation is not reached during absorber processing, resulting in lower doping. Further studies are needed to reveal the exact relationship between doping, stoichiometry and Na distribution.…”
Section: Origin Of V Oc àJ Sc Anticorrelation With Varying Stoichiometrymentioning
confidence: 99%
“…This could be linked with the spatial origin of the defects. From atom probe tomography (APT) measurements it is known that PDT has the effect that Rb [15] and other alkali [16] segregate at grain boundaries and interfaces. In this study, only a reduction of the trap density of E1 and not H2 is observed.…”
mentioning
confidence: 99%
“…In contrast, the H2 trap is located in grain interior regions or is distributed more homogeneously through the layer. Alkali elements have a limited solubility in CIGS grain interiors [16] and therefore a significant passivation of the point defect H2 is not possible. Segregated at grain boundaries, the Rb atoms can occupy the defects and passivate them.…”
mentioning
confidence: 99%
“…A comparison with the HAXPES results presented above indicates that there may be a correlation between the observed compositional changes and device properties for the CsF and RbF treated samples. The higher V OC for RbF as compared to CsF treated samples could possibly be connected to higher Ag surface content (thus higher acceptance of alkali elements in the absorber 33 and lower VBM expected), together with lower Cu content (known to promote band gap widening in CIGS). Still, no significant difference in the VB spectra has been observed between the RbF and CsF treated samples as discussed above, which might be masked by the increased bulk sensitivity of the HAXPES measurements, and thus the shift cannot be resolved.…”
Section: Resultsmentioning
confidence: 99%